THEQUALITY OF THEPROFESSIONAL TRAININGIN THE NATIONAL UNIVERSITY OF ENGINEERING (UNI). CASE OFTHE FACULTY OF INDUSTRIAL ENGINEERING AND SYSTEMS - Falconí Vasquez, Rodolfo (2005)
This study presents methodologies and analysis techniques such as: Strategic Planning, Quality Management, the European Foundation for the Quality Management Method (EFQM), the Balanced Scorecard Method (BSC) and the Accreditation Board for Engineering and Technology approaches (ABET), used for the implementation of the quality in the university teaching.